Leaching behaviour and ecotoxicity evaluation of chars from the pyrolysis of forestry biomass and polymeric materials - Bernardo, Maria S. (2014)
The main objective of this study was to assess the environmental risk of chars derived from the pyrolysis of mixtures of pine, plastics, and scrap tires, by studying their leaching potential and ecotoxicity. Relationships between chemical composition and ecotoxicity were established to identify contaminants responsible for toxicity. Since metallic contaminants were the focus of the present study, an EDTA washing step was applied to the chars to selectively remove metals that can be responsible for the observed toxicity. The results indicated that the introduction of biomass to the pyrolysis feedstock enhanced the acidity of chars and promote the mobilisation of inorganic compounds. Chars resulting from the pyrolysis of blends of pine and plastics did not produce ecotoxic eluates. A relationship between zinc concentrations in eluates and their ecotoxicity was found for chars obtained from mixtures with tires. A significant reduction in ecotoxicity was found when the chars were treated with EDTA, which was due to a significant reduction in zinc in chars after EDTA washing.